A case report of a Wada test after dominant hemisphere multiple hippocampal transections: Pathophysiology of confusion after amobarbital injection - Patrick Landazuri; Jonathan Miller; Hans Lüders (Epilepsy and Behavior Case Reports, 2014)
Dialepsis is defined as a predominant alteration of consciousness with preservation of motor tone and the ability to perform movements. While dialepsis is a common feature of both focal and generalized epilepsies, its precise symptomatogenic zone and pathogenesis remain undefined. This case report describes a patient who underwent intracarotid amobarbital procedures before and after dominant hemisphere multiple hippocampal transections. From our observations, we propose a possible pathogenesis for the generation of dialeptic seizures.